2016
DOI: 10.1007/s10930-016-9659-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cytoskeleton as a Mitochondrial Decay Signature in the Retinal Pigment Epithelium

Abstract: Mitochondria mediate energy metabolism, apoptosis, and aging, while mitochondrial disruption leads to age-related diseases that include age-related macular degeneration (AMD). Descriptions of mitochondrial morphology have been non-systematic and qualitative, due to lack of knowledge on the molecular mechanism of mitochondrial dynamics. The current study analyzed mitochondrial size, shape, and position quantitatively in retinal pigment epithelial cells (RPE) using a systematic computational model to suggest mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Our previous data suggested the potential cell death mechanisms in the retina and RPE under oxidative stress [8,9,12,13,16,2830]. We demonstrated that oxidative stress may trigger induction of anti-apoptotic erythropoietin, JAK2, and BCL-xL, as well as pro-apoptotic caspases [28,29,31].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our previous data suggested the potential cell death mechanisms in the retina and RPE under oxidative stress [8,9,12,13,16,2830]. We demonstrated that oxidative stress may trigger induction of anti-apoptotic erythropoietin, JAK2, and BCL-xL, as well as pro-apoptotic caspases [28,29,31].…”
Section: Discussionmentioning
confidence: 85%
“…Early signaling molecules under oxidative stress, including erythropoietin (EPO), crystallins, vimentin, protein phosphatase 2A (PP2A), hypoxia inducible factor-1 (HIF1), JAK2, prohibitin, RPE65, and nitric oxide synthase (NOS), are modulated and hyperphosphorylated in vitro and in vivo [79]. For instance, phosphorylations of crystallin and vimentin may participate in the pathogenesis of AMD by forming soft drusen with longer chain phosphatidylcholine and cholesteryl esters [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Cells were grown on sterile glass cover slips using DMEM/F12 medium with 10% FBS and 1% penicillin/streptomycin (Hyclone) in 5% CO 2 incubator at 37°C. Cells were treated under oxidative stress or intense light as previously reported [9][10][11][18][19][20]. Cells were washed with PBS and incubated with MitoTracker Orange CMTMRos (100 nM, Molecular Probes, Carlsbad, CA) in serum-free culture medium (30 min, 37°C), followed by washing (PBS) and fixing (10% formaldehyde, 30 min, room temperature).…”
Section: Immunocytochemical Analysismentioning
confidence: 99%
“…Previous data demonstrated that Hsp70 (c-Jun N-terminal kinase), crystallins (Akt), and the increased expression of VDAC might be involved in AMD progression [22][23][24][25][26]. Altered phosphorylations of mitochondrial heat shock protein mtHsp70, αA/aB crystalline, vimentin, and ATP synthase were observed in RPE cell death under oxidative stress [9,22,[27][28][29]. Retinoid-binding proteins, including CRABP, RPE65, and RLBP1, could be involved in the advanced stages of AMD [30][31][32].…”
Section: Immunocytochemistry Of Mitochondrial Trafficking Using Tubulmentioning
confidence: 99%
“…Previously, we showed that the visual cycle might be coordinated in a circadian-dependent manner to effectively protect the retina from the detrimental effects of light-induced ROS damage [2], [3], [13]. We hypothesize that these conditions may regulate protection mechanisms in the retina by anti-apoptosis, and that melatonin-targeted molecules may play crucial roles in maintaining neuroretinal architecture.…”
Section: Introductionmentioning
confidence: 99%